"Sweetened Condensed Milk" : from promotional media to corporate crime - Musriko Musriko; Febriansyah Febriansyah (Journal of Law Science, 2024)
Promotion is defined as the activity of introducing or disseminating information about goods and/or services, to attract consumers' buying interest in goods and/or services that will and are currently transacting. Promotion has a significant impact in influencing consumers' decision to purchase a product. The need for regulations governing consumer protection is intended so that in promotional activities the public is not trapped in a rotating promotional media, whether through words, images or other things. Recently there has been a polemic regarding the use of the word "milk" in advertisements or packaging for sweetened condensed milk products by business actors. Based on this, in this article the author will examine in depth how promotional media can lead to corporate criminal acts, especially in connection with the use of the word "milk" in sweetened condensed milk. To answer a problem, the author uses legal research methods assisted by statutory and doctrinal approaches. The results of the research show that promotional media that outlines legal provisions as regulated in the Consumer Protection Law, as well as other laws and regulations, is a form of criminal act that can require criminal liability, not only for the person involved, but also for the corporation